Does littoral substrate affect macroinvertebrate assemblages in Mediterranean lakes? - Mavromati, E.; Kemitzoglou, D.; Tsiaoussi, V. (2023)
Mavromati, E., D. Kemitzoglou, and V. Tsiaousi. 2023. Does littoral substrate affect macroinvertebrate assemblages in Mediterranean lakes? Aquatic Ecology (2023). https://doi.org/10.1007/s10452-023-10037-7